2015
DOI: 10.1371/journal.pone.0125914
|View full text |Cite
|
Sign up to set email alerts
|

DNA Priming for Seasonal Influenza Vaccine: A Phase 1b Double-Blind Randomized Clinical Trial

Abstract: BackgroundThe efficacy of current influenza vaccines is limited in vulnerable populations. DNA vaccines can be produced rapidly, and may offer a potential strategy to improve vaccine immunogenicity, indicated by studies with H5 influenza DNA vaccine prime followed by inactivated vaccine boost.MethodsFour sites enrolled healthy adults, randomized to receive 2011/12 seasonal influenza DNA vaccine prime (n=65) or phosphate buffered saline (PBS) (n=66) administered intramuscularly with Biojector. All subjects rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
1
17
1
Order By: Relevance
“…In previous influenza vaccine trials involving healthy adults, priming with a DNA vaccine and following with a monovalent inactivated boost proved more effective than an inactivated prime-boost regimen at establishing an antibody response against emerging subtypes of avian origin, including H5 and H7 [ 19 , 21 ]. In a separate trial in healthy adults involving a DNA prime-IIV3 boost regimen with seasonal strains of influenza (H1, H3, and B), no significant improvement was observed compared to a placebo prime-IIV3 boost group, presumably due to pre-existing immune responses [ 23 ]. Therefore, we evaluated the DNA prime-IIV3 boost regimen in children and adolescents in an attempt to examine the safety and immunogenicity of the DNA prime-IIV3 boost in a more naïve population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous influenza vaccine trials involving healthy adults, priming with a DNA vaccine and following with a monovalent inactivated boost proved more effective than an inactivated prime-boost regimen at establishing an antibody response against emerging subtypes of avian origin, including H5 and H7 [ 19 , 21 ]. In a separate trial in healthy adults involving a DNA prime-IIV3 boost regimen with seasonal strains of influenza (H1, H3, and B), no significant improvement was observed compared to a placebo prime-IIV3 boost group, presumably due to pre-existing immune responses [ 23 ]. Therefore, we evaluated the DNA prime-IIV3 boost regimen in children and adolescents in an attempt to examine the safety and immunogenicity of the DNA prime-IIV3 boost in a more naïve population.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the difference in immune response observed between studies in healthy adults against avian subtypes of influenza where a significantly improved response was observed following priming with DNA [ 19 , 21 ], and the single study investigating seasonal strains of influenza where no difference in titers was observed [ 23 ], was the high levels of pre-existing immunity to the seasonal strains in the adult population. This led to the possibility that an improved response following DNA-IIV3 vaccination could be observed in the more naïve pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 37 , 38 Previous experience with DNA vaccines shows them to be safe, well-tolerated and immunogenic as a priming vaccine, and they may be optimally suited for pre-pandemic scenarios where pre-existing immunity is lacking in the population. 22 , 28 , 38 40 …”
Section: Discussionmentioning
confidence: 99%